Advanced Supercritical Fluids Technologies - Pioro, Igor (IntechOpen, 2020)
Using SuperCritical Fluids (SCFs) in various processes is not new, because Mother Nature has been processing minerals in aqueous solutions at critical and supercritical pressures for billions of years. Somewhere in the 20th century, SCFs started to be used in various industries as working fluids, coolants, chemical agents, etc. Written by an international team of experts and complete with the latest research, development, and design, Advanced Supercritical Fluids Technologies is a unique technical book, completely dedicated to modern and advanced applications of supercritical fluids in various industries.Advanced Supercritical Fluids Technologies provides engineers and specialists in various industries dealing with SCFs as well as researchers, scientists, and students of the corresponding departments with a comprehensive overview of the current status, latest trends and developments of these technologies.Dr Igor Pioro is a professor at the University of Ontario Institute of Technology, Canada, and the Founding Editor of the ASME Journal of Nuclear Engineering and Radiation Science.